The Study of Prefabricated Construction Methods for Mass Tread Housing Construction. Case Study: Dian Sukolilo Regency Housing, Surabaya - stefanie susanto (Program Studi Magister Teknik Sipil - Petra Christian University, 2019)
This paper discusses the prefabricated construction method by taking a case study of Dian Sukolilo Regency housing construction, Surabaya. Prefabricated construction methods are able to provide faster construction times and better quality. Stages of research will be carried out by processing real data with a simulation calculation approach to obtain the calculation of the budget plan and estimated time of construction using the prefabrication method. The main variables that influence this prefabricated construction method are four namely cost, time, quality and number of units. The increasing number of units will reduce the cost of construction of the construction unit using the prefabrication method. The results of each research calculation will guide the interview to find out the response of the housing developer to the prefabricated construction method whose results will be the conclusion of the study.